Dietary Total Antioxidant Capacity and Oxidative Stress in Patients with Type-2 Diabetes - Çetiner, Özlem; Şendur, Süleyman Nahit; Yalçın, Tuba; Bayraktar, Miyase; Rakıcıoğlu, Neslişah (Progress in Nutrition, 2021)
Abstract. Background/Aim.Reactive oxygen species can disrupt normal cellular functions by damaging DNA, protein, and lipid structures of the cell. Some antioxidant molecules may protect the body against reactive oxygen species. We aimed to investigate the relationship between the dietary intake of antioxidants and oxidative DNA damage in diabetic patients. Materials and Methods: A total of 85 individuals were included in the study, of which 30 were newly diagnosed with type-2 diabetes, 30 were formerly diagnosed with type-2 diabetes, and 25 were healthy individuals. Twenty-four-hour dietary recalls were recorded for 3 consecutive days. Dietary total antioxidant capacity and dietary oxidative balance scores were calculated according to these records. Spot urine samples were collected and analyzed for 8-hydroxy-2ʹ deoxyguanosine/creatinine. Results: Dietary total antioxidant capacity, estimated via different methods, was higher in the controls than that in patients with type-2 diabetes (p